2021
DOI: 10.1002/ijgo.14023
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic variation in causes of stillbirth in high‐income countries: A systematic review and meta‐analysis

Abstract: Stillbirth is a devastating pregnancy outcome that not only has emotional, psychological, and financial consequences for affected women and families, 1 but also impacts individual healthcare workers, health care networks and the wider society. 2 The global stillbirth rate is estimated to be 18.4 per 1000 births, equating to approximately 2.6 million stillbirths every year. 3 The World Health Organization's (WHO) Every Newborn: An Action Plan to End Preventable Deaths aims to reduce the stillbirth rate to ≤12 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…also found that South Asian women in New Zealand were more likely to have placentas showing histologic chorioamnionitis or chorionic vasculitis than other ethnicities 26 . This is consistent with a recent systematic review by Bhat et al ., which reported women of Asian and South Asian ethnicities were most likely to suffer stillbirth caused by complications of the ‘placenta, cord and membranes’ compared to other ethnicities 11 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…also found that South Asian women in New Zealand were more likely to have placentas showing histologic chorioamnionitis or chorionic vasculitis than other ethnicities 26 . This is consistent with a recent systematic review by Bhat et al ., which reported women of Asian and South Asian ethnicities were most likely to suffer stillbirth caused by complications of the ‘placenta, cord and membranes’ compared to other ethnicities 11 …”
Section: Discussionmentioning
confidence: 99%
“…Second, use of well‐recognised classification systems such as the PSANZ‐PDC allows standardised and ready comparisons to be made between cohorts and studies. Third, we did not use surrogate markers of ethnic identity such as language or mother tongue, an identified limitation in other studies; 11 instead, ethnicity was self‐identified by women. Using self‐identified ethnic categories also omitted any possible bias that may be introduced by a possible third party assigning ethnicity, where assumptions based on surname or language may have been introduced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations